Epidemiology of Hyponatraemia among Elderly Patients with Lower Respiratory Tract Infection - Raju, B; Rishab, A; Vikram, K; Vaibhav, T; Sharat, T; Kopal, G; Santosh, K; Shreyas, A (Bangladesh Journal of Medicine, 2019)
Background: Decrease in serum sodium concentration is frequent observation among hospitalised elderly patients. The common causes for hyponatremia are degenerative physiology, dehydration, medications and infections. Hence the present study was undertaken to know the extent of hyponatremia among elderly with Lower Respiratory Tract Infections. Objectives: The present study was undertaken to assess the prevalence of hyponatremia in lower respiratory tract infection among geriatric age group and to determine the association between severity of hyponatraemia and LRTI. Methods: This was hospital based cross sectional study carried out in the Department of General Medicine of a tertiary care teaching hospital situated in north Karnataka, India during November 2016 to May 2018. 100 elderly patients (age e” 60 years) with history of cough for more than four to five days, clinical findings and X-ray findings suggestive of LRTI, were selected for the study. Results: In the present study 59% comprised of male whereas females constituted 41%. The prevalence of hyponatraemia among elderly patients with LRTI was 45%. The most common cause of hyponatraemia was GI loss (vomiting) 53.33%, Euvolemic hyponatramia 51.11%. The mean age was 69.99±8.44 years. Most of the patients were aged between 61 to 70 years. .Hyponatraemia was not associated with sex, age and type of LRTI. Duration of hospital stay was significantly longer in patients with hyponatraemia compared to those who did not develop hyponatraemia. Conclusion: Hyponatraemia among elderly individuals with LRTI is higher as compared to other age group hence leading to prolonged duration of hospitalisation. Bangladesh J Medicine Jan 2020; 31(1) : 13-17